2005
DOI: 10.1111/j.1600-0722.2005.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic protein expression patterns during intraoral wound healing in the rat

Abstract: Wound healing after cleft palate surgery is often associated with impairment of maxillary growth and dento-alveolar development. Wound contraction and scar tissue formation contribute strongly to these effects. In vitro studies have revealed that fibroblasts isolated during different phases of palatal wound healing show phenotypical differences. They change from a quiescent to an activated state and then partly back to a quiescent state. In this study, we evaluated the existence of fibroblast phenotypes at sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Diffuse distribution in cytoplasm shows its inactive free form, at least with respect to its actinbinding potential (71) as found in less motile corneal cells (72). In our study, lack of vinculin expression in migratory cells contrary to the presence of strong vinculin expression in the cells residing in epi and subretinal membranes supports that vinculin has a functional role in regulating motility (67,68,73), and vinculin seems to be downregulated in motile cells (68) as in activated fibroblast state in wound healing (74). Molitor et al showed vinculin expression intracellularly in ERMs in human specimens and they suggested that besides of actin and myosin, intracellular vinculin ex-pression is responsible for the contraction of ERMs (75).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Diffuse distribution in cytoplasm shows its inactive free form, at least with respect to its actinbinding potential (71) as found in less motile corneal cells (72). In our study, lack of vinculin expression in migratory cells contrary to the presence of strong vinculin expression in the cells residing in epi and subretinal membranes supports that vinculin has a functional role in regulating motility (67,68,73), and vinculin seems to be downregulated in motile cells (68) as in activated fibroblast state in wound healing (74). Molitor et al showed vinculin expression intracellularly in ERMs in human specimens and they suggested that besides of actin and myosin, intracellular vinculin ex-pression is responsible for the contraction of ERMs (75).…”
Section: Discussionsupporting
confidence: 58%
“…Scarcity of α-SMA positive cells may represent recent myofibroblastic differentiation in these cells or reduced population of α-SMA positive cells as the traces of contractility evolved. It is shown that myofibroblasts derived from granulation tissue fibroblasts express transiently α-SMA (89) so that α-SMA positive cells show a peak in granulation tissue phase and than decline gradually at a later phase (74,90).…”
Section: Discussionmentioning
confidence: 99%
“…Wound contraction and scar tissue formation strongly contribute to these unwanted effects, 6,7 which are produced by fibroblasts and myofibroblasts 6 . We have previously reported that palatal fibroblasts show different phenotypes in different phases of the wound‐healing process 7,8 . These differences seem to coincide with changes in the functions of fibroblasts and myofibroblasts during wound contraction and scar tissue formation.…”
mentioning
confidence: 99%
“…As focal adhesions are important for fibroblast migration and adhesion, 20 we expected to find changes in the expression of focal adhesion proteins, such as vinculin in fibroblasts treated with LNO. In fact, it has been described that, in fibroblasts from wounded areas, the increased expression of vinculin is correlated with a higher migratory capacity 20,27 . It has been reported that during cell migration, vinculin and stress fibers play a key role in the integrin‐mediated interaction of fibroblasts with the ECM 28 .…”
Section: Discussionmentioning
confidence: 99%